Dampak Industri Kecil dan Menengah pada Kesempatan Kerja dan Pendapatan per Kapita - Saparuddin, M (Jurnal Trikonomika, 2011)
The purpose of this research is to review and analyze the influence of GDP, investment, education and training, and government policies on the growth of small and medium enterprises. Subsequently, this research aims to review and analyze the effect of GDP, investment, small and medium enterprises, and employment opportunities on per capita income. The next purpose of this research is to review and analyze the influence of GDP, investment, small and medium enterprises on employment opportunities. This research is categorized descriptive and verifying research. The method used is survey method and it uses simultaneous equation model in the period of 6 years in 13 districts in South Sulawesi. The results showed that (a) GDP, investment, education and training, and government policies significantly affect the growth of small and medium enterprises; (b) GDP, investment, small and medium enterprises, and employment opportunities significantly affect per capita income; and (c) GDP, investment, and small and medium enterprises significantly affect the employment opportunities.